Diagnosis and management of septal deviation and nasal valve collapse - a survey of Canadian otolaryngologists - Wang, Yiqiao; Bonaparte, James P (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Management of nasal valve collapse (NVC) in patients with a septal deviation can be challenging. Our objective was to determine the opinions of Canadian Otolaryngologists regarding the diagnosis and management of nasal obstruction in patients with septal deviation and NVC. Methods A twenty-question survey was developed for the purpose of our study. Questions were divided into the following areas: diagnosis, management and prognosis. We included all otolaryngologists who were members of the Canadian Society of Otolaryngology. Results The response rate to our survey was 18%. The most commonly identified cause of a failed septoplasty was incomplete septoplasty (41.9%), followed by nasal valve collapse (25.6%). The Cottle manoeuvre (62.8%) and visual inspection (39.5%) were noted to be the most important diagnostic tools for external and internal NVC respectively. However, physicians often rely on a variable number of different examinations when making a diagnosis of nasal valve collapse. When evaluating which patients with a septal deviation also required nasal valve surgery, 27.9% of responders believed the current physical examination methods provided a high accuracy, while 55.8% indicated moderate accuracy and 16.3% indicated low accuracy. Compared to other subspecialties in Otolaryngology, Facial Plastic and Reconstruction Surgeons noted higher septoplasty failure rates in patients with co-morbid NVC. Conclusions NVC is an important concern for otolaryngologists performing septoplasty. Although most physicians believe that the physical exam provides a moderate effectiveness when predicting who requires a functional rhinoplasty, diagnostic methods used for NVC is varied and inconsistent.